1995
DOI: 10.1126/science.270.5240.1354
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Characterization of a Coactivator for the Steroid Hormone Receptor Superfamily

Abstract: A yeast two-hybrid system was used to identify a protein that interacts with and enhances the human progesterone receptor (hPR) transcriptional activity without altering the basal activity of the promoter. Because the protein stimulated transactivation of all the steroid receptors tested, it has been termed steroid receptor coactivator-1 (SRC-1). Coexpression of SRC-1 reversed the ability of the estrogen receptor to squelch activation by hPR. Also, the amino terminal truncated form of SRC-1 acted as a dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,352
7
13

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,220 publications
(1,419 citation statements)
references
References 23 publications
47
1,352
7
13
Order By: Relevance
“…Since this breast cancer cDNA encoded a nuclear receptor-binding auxiliary protein (Segars et al, 1993), we called the gene brx. Overlapping cDNA clones were consistent with a 5.3 kilobase cDNA encoding a 1428 amino acid protein with a 168 kilodalton predicted molecular mass distinct from proteins reported to bind nuclear hormone receptors (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994;Jacq et al, 1994;Chen and Evans, 1995;Horlein et al, 1995;Onate et al, 1995;Le Douarin et al, 1995;Baniahmad et al, 1995).…”
Section: Identi®cation and Cloning Of Brx Cdnasupporting
confidence: 54%
See 1 more Smart Citation
“…Since this breast cancer cDNA encoded a nuclear receptor-binding auxiliary protein (Segars et al, 1993), we called the gene brx. Overlapping cDNA clones were consistent with a 5.3 kilobase cDNA encoding a 1428 amino acid protein with a 168 kilodalton predicted molecular mass distinct from proteins reported to bind nuclear hormone receptors (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994;Jacq et al, 1994;Chen and Evans, 1995;Horlein et al, 1995;Onate et al, 1995;Le Douarin et al, 1995;Baniahmad et al, 1995).…”
Section: Identi®cation and Cloning Of Brx Cdnasupporting
confidence: 54%
“…For example, gene activation by nuclear hormone receptors (NHRs) has recently been shown to include additional proteins that associate directly with receptors, including the estrogen receptor (see : Horwitz et al, 1996;Katzenellenbogen et al, 1996). Biochemical and interactive cloning methods have led to isolation of 120 (Le Douarin et al, 1995), 125 (Onate et al, 1995), 140 (Cavailles et al, 1994(Cavailles et al, , 1995Halachmi et al, 1994), 160 (Halachmi et al, 1994;Cavailles et al, 1994), 168 (Chen and Evans, 1995) and 270 (Horlein et al, 1995) kDa proteins shown to associate with ligand-bound NHRs and function as positive (co-activators) or negative (corepressors) of nuclear receptor action by modulating interaction with the basal transcription complex. In addition, CBP (and related protein p300) has been described as a`co-integrator' of hormone receptor function through interaction with the nuclear receptor binding protein p160, TFIIB, and Jun/Fos (Kamei et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We conclude therefore that SRC-1 is the most potent cofactor in our assay and therefore likely to be acting directly at the ERBB2 enhancer. Moreover both SRC-1 and TIF2, although widely expressed, have previously been identi®ed as competable, limiting factors particularly in the context of the squelching of progesterone receptor transactivation in the presence of ectopic ER expression (Onate et al, 1995;Voegel et al, 1996). Signi®cantly, both proteins are expressed at very modest levels in most breast tumour derived cell lines (Anzick et al, 1997;Berns et al, 1998) and levels of SRC-1 are also particularly low in patients who fail to respond to tamoxifen therapy (Berns et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…ER may be able to initiate transcription by interacting with proteins that play a role in chromatin remodeling or initiation of transcription. Recently, it was demonstrated that estrogen-bound ER associates with coactivators such as SRC-1A that possess intrinsic histone acetyltransferase (HAT) activity and recruits other HATs including CBP and p/CAF to chromatin (Onate et al, 1995;Spencer et al, 1997;Smith et al, 1996;Jenster et al, 1997). In addition, CBP links steroid hormone receptors to components of the basal transcription machinery including RNA polymerase II, TATA-binding protein, TFIIB and TFIID (Kee et al, 1996;Abraham et al, 1993;Xing et al, 1995).…”
Section: Demethylation Of the Pr Cpg Island Is Not Required For Reactmentioning
confidence: 99%
“…MDA-MB-231 cells were transiently transfected with pCMV-ER, an expression vector for ER, in the presence or absence of SRC-1 (.8). SRC-1 (.8) is a dominant negative inhibitor of SRC-1A which interferes with the interaction of ER and SRC-1A, and leads to a partial inhibition of steroid hormone-responsive reporter gene activity as assayed in transiently transfected cells (Onate et al, 1995). Three independent experiments were performed in triplicate and results from one representative experiment are shown in Figure 4.…”
Section: Demethylation Of the Pr Cpg Island Is Not Required For Reactmentioning
confidence: 99%